State of terror [compact disc, unabridged] : a novel - Clinton, Hillary Rodham; Penny, Louise (Simon & Schuster, 2021)
This high-stakes thriller follows a novice Secretary of State who has joined the administration of her rival, a president inaugurated after four years of American leadership that shrank from the world stage. A series of terrorist attacks throws the global order into disarray, and the secretary is tasked with assembling a team to unravel the deadly conspiracy, a scheme carefully designed to take advantage of an American government dangerously out of touch and out of power in the places where it counts the most.